Investigating students' conceptual change about colour in an innovative research-based teaching sequence - Ana Rita Lopes Mota; João Lopes dos Santos (Investigações em Ensino de Ciências, 2018)
This paper is the second part of a multiphase study investigating the impact of a mathematical model, the Addition Table of Colours (ATC), in the learning of colour phenomena. The ATC instruction was undertaken in several 8th grade classes in three different Portuguese schools (250 students) and included collaborative activities through Lab stations model. In the control group (204 students), the colour phenomena were taught in the traditional way, with the goals set by the teachers, without any intervention of the project. The two groups of students were compared in terms of content knowledge acquired in the learning of this subject through comparison and analysis of their pre and post-tests. Quantitative analyses of the pre/post-tests revealed five variants of students’ representations about this phenomenon. We found that the ATC model, inserted in an interactive and carefully designed teaching environment, is more effective in promoting conceptual change and scientific understandings of colour phenomena.